Functional outcome after total hip replacement following 30 years neglected posterior hip dislocation: a rare case report - Purvance, Ivander; Dusak, Wayan Suryanto; Putra Stanu, Gusti Ngurah; Dewi Astawa, Ni Made Puspa (International Journal of Research in Medical Sciences, 2020)
Neglected traumatic dislocations of the hip is one of disabling condition in lower extremity which are seldom found in adults. However, in developing countries, neglected-unreduced traumatic dislocations are not uncommon. Total hip replacement (THR) still remains a recommendation for the treatment of neglected hip dislocation which occurs more than 3 months. A 45- years-old female came to the outpatient clinic complaining pain on her right hip with history of trauma 30 years before, but instead of seeking medical treatment, she went to bonesetter instead. On physical examination, there is 5 cm leg length discrepancy, and the patient walked with limping gait. Conventional x-ray confirmed persistent dislocation of the right hip. A soft tissue release procedure and femoral neck osteotomy with skeletal traction was done before, followed by delayed THR two months after. The patient’s functional status was improved, and the HHS score increased from 48 to 87. The patient had no pain or significant complaints, except for a finding of mild residual Trendelenburg gait.